A preliminary study of pneumonia etiology among hospitalized children in Kenya. - Hammitt, L; Kazungu, S; Morpeth, S; Gibson, D; Mvera, B; Brent, A; Mwarumba, S; Onyango, C; Bett, A; Akech, DO; Murdoch, DR; Nokes, D; et al. (2012)
BACKGROUND: Pneumonia is the leading cause of childhood death in the developing world. Higher-quality etiological data are required to reduce this mortality burden. METHODS: We conducted a case-control study of pneumonia etiology among children aged 1-59 months in rural Kenya. Case patients were hospitalized with World Health Organization-defined severe pneumonia (SP) or very severe pneumonia (VSP); controls were outpatient children without pneumonia. We collected blood for culture, induced sputum for culture and multiplex polymerase chain reaction (PCR), and obtained oropharyngeal swab specimens for multiplex PCR from case patients, and serum for serology and nasopharyngeal swab specimens for multiplex PCR from case patients and controls. RESULTS: Of 984 eligible case patients, 810 (84%) were enrolled in the study; 232 (29%) had VSP. Blood cultures were positive in 52 of 749 case patients (7%). A predominant potential pathogen was identified in sputum culture in 70 of 417 case patients (17%). A respiratory virus was detected by PCR from nasopharyngeal swab specimens in 486 of 805 case patients (60%) and 172 of 369 controls (47%). Only respiratory syncytial virus (RSV) showed a statistically significant association between virus detection in the nasopharynx and pneumonia hospitalization (odds ratio, 12.5; 95% confidence interval, 3.1-51.5). Among 257 case patients in whom all specimens (excluding serum specimens) were collected, bacteria were identified in 24 (9%), viruses in 137 (53%), mixed viral and bacterial infection in 39 (15%), and no pathogen in 57 (22%); bacterial causes outnumbered viral causes when the results of the case-control analysis were considered. CONCLUSIONS: A potential etiology was detected in >75% of children admitted with SP or VSP. Except for RSV, the case-control analysis did not detect an association between viral detection in the nasopharynx and hospitalization for pneumonia.